Associations of atrial fibrillation with renal function decline in patients with chronic kidney disease. Issue 6 (30th June 2021) - Chen, Tz-Heng; Chu, Yuan-Chia; Ou, Shuo-Ming; Tarng, Der-Cherng
Abstract : Background: Chronic kidney disease (CKD) is known to increase the risk of atrial fibrillation (AF) development, but the relationship between AF and subsequent renal function decline in patients with CKD is not well understood. In this study, we explored the role of AF on renal outcomes among patients with CKD. Methods: In a retrospective hospital-based cohort study, we identified patients with CKD aged ≥20 years from 1 January 2008 to 31 December 2018. The patients were divided into AF and non-AF groups. We matched each patient with CKD and AF to two non-AF CKD controls according to propensity scores. The outcomes of interest included estimated glomerular filtration rate (eGFR) decline of ≥20%, ≥30%, ≥40% and ≥50%, and end-stage renal disease (ESRD). Results: After propensity score matching, 6731 patients with AF and 13 462 matched controls were included in the analyses. Compared with the non-AF group, the AF group exhibited greater risks of eGFR decline ≥20% (HR 1.43; 95% CI 1.33 to 1.53), ≥30% (HR 1.50; 95% CI 1.36 to 1.66), ≥40% (HR 1.62; 95% CI 1.41 to 1.85) and ≥50% (HR 1.82; 95% CI 1.50 to 2.20), and ESRD (HR 1.22; 95% CI 1.12 to 1.34). Higher CHA2 DS2 -VASc scores were associated with greater risks of eGFR decline and ESRD. Conclusions: In patients with CKD, AF was associated with greater risks of subsequent renal function decline. CHA2 DS2 -VASc scores may be a useful risk stratification scheme for predicting the risk of renal function decline.